Effects of academic programs on stressors and coping strategies among university students - Amponsah, Kwaku Darko; Adjei-Boateng, Emmanuel; Addae, David; Commey-Mintah, Priscilla (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study investigated the psychological aspects of stress and coping strategies among college students in the post-implementation period of Ghana’s free senior high school (SHS) policy. Focusing on the Department of Teacher Education at the University of Ghana, the research surveyed 270 students from diverse programs. Using psychological tools like the perceived stress scale and the brief coping orientation to problem experienced (COPE), the study employed statistical methods, including mean, standard deviation, Pearson product correlation, and hierarchical linear and multiple regression, to analyze the data. The findings revealed commonalities and differences in stressors and coping techniques across academic programs, indicating that the unique demands of each program influenced students’ experiences. The study did not find a significant moderating effect of gender on the stressor-coping relationship. The results highlighted the importance of recognizing program-specific variations for targeted stress management support, illustrating the interplay between stressors, coping mechanisms, and academic programs. The study concluded by emphasizing the psychological implications of these findings, offering valuable insights into the complexities of stress and coping among college students, particularly within the context of educational reforms.